IMPACT OF VITAMIN D DEFICIENCY ON REPRODUCTIVE HORMONES AND MENSTRUAL IRREGULARITIES IN WOMEN OF REPRODUCTIVE AGE - Musarrat Manzoor; Mamoona Sarwar; Uswa Mansoor; M. Shakil Zari Khawri Siddiqui; Amir Jalal; Waqas Qurshi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: In addition to its classical effect in bone metabolism, vitamin D is crucial in the process of reproductive physiology, having an effect on ovarian steroidogenesis, gonadotropin secretion, and endometrial functioning. Vitamin D deficiency is very common amongst those women in South Asia of reproductive age and could be a cause of menstrual disorders and hormonal problems. Objectives: The aim of the study was to assess the relationship between vitamin D deficiency, reproductive hormone profiles and menstrual abnormalities in women of reproductive age who visited tertiary care hospitals in Pakistan. Methods: The study was conducted as a cross-sectional observational study between June 2024 and April 2025 at the Muhammad Medical College and Hospital, Mirpurkhas, and Ittefaq Hospital Trust, Lahore. One hundred and fifty women of the ages 18 to 45 years with menstrual irregularities were recruited. Measures were done on serum vitamin D [25(OH)D], follicle-stimulating hormone (FSH), luteinizing hormone (LH), estradiol and progesterone. Deficiency in vitamin D was considered as less than 20 ng/ml, insufficiency as 20-29 ng/ml and sufficiency 30gm/dl or more. The statistical analysis has been done in SPSS version 26, and p <0.05 is taken to be significant. Results: 58.7 percent of the respondents were found to be vitamin D deficient, 24.7 percent insufficient and only 16.6 percent sufficient. There was a report of menstrual irregularities in 64% of the women with most being oligomenorrhea (40.6%). Vitamin D deficiency was significantly associated with irregularities in menstruation (75% vs. 40% in sufficient group p=0.01). The deficient women had elevated levels of FSH (9.8 ± 2.5 IU/L) and LH (12.6 ± 3.7 IU/L), an elevated LH/FSH ratio, and a reduced level of estradiol (85.4 ± 21.7 pg/mL) and progesterone (6.2 ± 1.8 ng/mL) than adequately endowed women. The correlation of Pearson revealed that vitamin D had a positive correlation with estradiol (r=0.41, p<0.001) and progesterone (r=0.46, p<0.001), but a negative correlation with LH (r= -0.35, p<0.01). Conclusion: The deficiency of vitamin D is very common in the women of childbearing age and is closely linked with menstrual cycles and negative changes in reproductive hormones. Routine screening and correction of vitamin D deficiency may also be a cost-effective measure to enhance reproductive health outcomes in such a population